ANALYSIS OF THE DEMAND FOR PRIVATE HEALTHCARE IN SOUTH AFRICA - DUNGA, Steven Henry (Studia Universitatis Babeș-Bolyai Oeconomica, 2019)
Access to a good and healthy life is a human right recognised globally. The fight to deal with poverty and food insecurity as the top two sustainable development goals (SDGs) under the global agenda 2030 can only be achieved if a majority of the world population is able to participate in economic activities. However, the provision of healthcare is complicated by the nature of the demand and supply function. There is inefficient provision due to the positive externalities associated with healthcare provision and consequently the social efficiency is not achieved, especially when private provision is considered, and therefore the need for government involvement. This paper analyses the demand for private healthcare in South Africa, using the data collected from a general household survey with a sample of 21601 households. The results of the logistic regression model show that the gender of the head of a household, income, food security status, age of head of household and social grant and pension status were among the significant predictors of demand for private healthcare. The study provides insights on how provision of healthcare should be tailored so as to achieve maximum efficiency in public provision of healthcare. JEL classification: I11, I15, I32, H41